Job Satisfaction in Mediating Work Discipline and Work Stress on Employee Work Productivity - Palahudin; Sri Harini; Nurul Amanah (International Journal of Educational and Life Sciences, 2024)
This study aims to analyze the effect of work discipline and stress on productivity through job satisfaction as an intervening variable at PT. XYZ. This quantitative research uses descriptive, verificative methods, path analysis, and Sobel test. Data collection was carried out through secondary and primary data from 80 employees using purposive sampling because the number of employees studied at the company was less than 100. The analysis was conducted using IBM SPSS25 software. The results of this study indicate that work discipline has a direct positive effect on job satisfaction, work stress has a direct negative effect on job satisfaction, work discipline has a direct positive effect on productivity, work stress has a negative effect on productivity, job satisfaction has a direct positive effect on.